Identification types and nutritional composition of traditional pig feed in rural areas of Timor Island and its influence on production efficiency - Suryani, Ni N.; Samba, Fredeicus D.; Nguru, David A.; Kertiyasa, I. K. Yoga; Widu, Asri A. (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
The use of traditional feed depends on the location of pig production. Information regarding traditional ration variations and nutritional content is not yet available, especially in rural areas of Timor Island. This research aims to identify the types and nutritional composition of traditional feeds used in rural pig rearing and to analyze their effects on production efficiency. The study was conducted in four villages in Taebenu District, Kupang Regency. This research used a descriptive observational design with a cross-sectional approach. Data collection was carried out to provide an overview of the types of traditional feed used, their nutritional composition, and their relationship to production efficiency. The data obtained were analyzed descriptively to describe the distribution of feed types and their nutritional composition; Pearson correlation tests and linear regression analyses were used to determine the relationships and their influence on production efficiency. The results of the research show that the composition of traditional feed across the four sampling locations is generally not much different and is highly diverse, which affects the diversity of its nutritional value. In this study, there was a positive correlation between nutrition and body weight gain and feed conversion. At the same time, regression analysis showed that crude protein and metabolic energy were the main factors that increased production efficiency. Based on the results of this research, it can be concluded that variations in local feed types result in differences in nutritional composition. The results of correlation analysis show that feed composition has a significant influence on the growth and production efficiency of pigs, crude protein and energy metabolism have a positive relationship with body weight gain and negative with feed conversion, while crude fiber has the opposite effect, regression analysis shows that crude protein and metabolic energy are the main factors that increase production efficiency, while crude fiber interferes with livestock performance.